Kelimpahan Brontispa longissimaGestro (Coleoptera: Chrysomelidae) dan Musuh Alami pada Tanaman Kelapa [The Abundance of Brontispa longissima Gestro (Coleoptera: Chrysomelidae) and Natural Enemies on Coconut Palms] - Novalisa T.E Lumentut; Sri Karindah; Meldy L.A Hosang (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
The abundance of Brontispa longissima and its natural enemies on coconut palms have been explored in North Minahasa,South Minahasa and Southeast Minahasa Districts in February 2012 - January 2013. The aims of the research were to study the abundance of B. longissima an natural enemies in the field. The research was conducted on unproduced coconut palm and productive coconut palm. Sampling is done randomly plated or Stratified random sampling using quadrant system. The results showed that the abundance of B. longissima fluctuated, the highest abundance occurred in August and September 2012 in unproductive palms. In productive palms, the highest abundance of B. longissima at the altitude of 300-600 m above sea level occurred in August 2012, which was 70.3 individuals / young leaves, then at altitude > 600 m above sea level occurred in September 2012, ie 64 individuals / young leaves, and at an altitude of <300 m above sea level occurred in June 2012, which is 62 individuals / young leaves. Brontispa longissima natural enemies found at altitudes <300 m above sea level, 300-600 m above sea level, and> 600 m above sea level in unproduced coconut palms are parasitoid Tetrastichus brontispae, Chelisoches morio predator, and entomopathogen Metarhizium anisopliae var. anisopliae. The natural enemies found in productive coconut palm at three different altitudes are Tetrastichus brontispae parasitoids, and Chelisoches morio predators. Entomopatogen M. aanisopliae var. anisopliae is not found on the productivecoconut palms at all three altitudes. The abundance of natural enemies and percentage of parasitism in the three different altitudes both in unproductive coconut palm and productive coconut palm was low is between 0.33-14.47%. This is due to the influence of abiotic and biotic factors on the abundance of B. longissima.ABSTRAK Kelimpahan Brontispa longissima dan musuh alaminya pada tanaman kelapa telah dieksplorasi di Kabupaten Minahasa Utara, Minahasa Selatan dan Minahasa Tenggara pada bulan Februari 2012 - Januari 2013. Penelitian bertujuan untuk mempelajari kelimpahan B. longissima dan musuh alaminya pada pertanaman kelapa. Penelitian dilaksanakan pada tanaman kelapa belum berproduksi dan tanaman kelapa produktif. Pengambilan contoh dilakukan secara acak berlapis atau Stratified random sampling dengan menggunakan sistem kuadran. Hasil penelitian menunjukkan bahwa kelimpahan B. longissima berfluktuasi, kelimpahan tertinggi terjadi pada bulan Agustus dan September 2012 pada tanaman belum berproduksi. Pada tanaman produktif kelimpahan B. longissima tertinggi berturut-turut pada ketinggian tempat 300-600 m dpl terjadi pada bulan Agustus 2012, yaitu 70,30 individu/pelepah, kemudian pada ketingian tempat >600 m dpl terjadi pada bulan September 2012, yaitu 64 individu/pelepah dan pada ketinggian <300 m dpl terjadi pada bulan Juni 2012, yaitu 62 individu/pelepah. Musuh alami B. longissima yang ditemukan pada ketinggian tempat <300 m dpl, 300- 600 m dpl, dan >600 m dpl pada tanaman belum berproduksi adalah parasitoid Tetrastichus brontispae, predator Chelisoches morio, dan entomopatogen Metarhizium anisopliae var. anisopliae. Musuh alami yang ditemukan pada tanaman berproduktif diketiga ketinggian tempat tersebut adalah parasitoid Tetrastichus brontispae, dan predator Chelisoches morio. Entomopatogen M. anisopliae var. anisopliae tidak dijumpai pada tanaman produktif diketiga ketinggian tempat tersebut. Kelimpahan musuh alami dan persentase parasitisme di tiga ketinggian tempat tersebut baik pada tanaman belum berproduksi maupun tanaman produktif ternyata rendah yaitu antara 0,33-14,47%. Hal ini disebabkan pengaruh faktor abiotik dan biotik terhadap kelimpahan B. longissima.